2020
DOI: 10.3329/bjpsy.v32i2.55126
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal factors among children with neurodevelopmental disorders attending tertiary care hospitals in Dhaka city

Abstract: Neurodevelopmental disorders (NDD) are public health burden worldwide. NDD causes disabilities and reduces the quality of life. Perinatal factors like maternal age, stress, maternal physical illnesses, birth complications, preterm birth, low birth weight and neonatal infections are the important risk factors for NDD. The objectives of the study were to determine the proportion of perinatal factors among children with neurodevelopmental disorders attending tertiary care hospitals in Dhaka city. This was a cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In this study, among NDI cases at 3-months, maternal illness was observed in 21 (52.5%) mothers, prolonged labour in 29 (72.5%) cases. Zohra et al [20] found maternal physical illness in 66.1 % cases and a follow up study on high risk newborn found that maternal illness during pregnancy and prolonged delivery had significant adverse neurodevelopmental outcome [21].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, among NDI cases at 3-months, maternal illness was observed in 21 (52.5%) mothers, prolonged labour in 29 (72.5%) cases. Zohra et al [20] found maternal physical illness in 66.1 % cases and a follow up study on high risk newborn found that maternal illness during pregnancy and prolonged delivery had significant adverse neurodevelopmental outcome [21].…”
Section: Discussionmentioning
confidence: 99%
“…Key fetal and neonatal factors included birth complications (82.6%), preterm birth (80%), low birth weight (75.6%), neonatal diseases (69.6%) like pneumonia (30%) and jaundice (20%), and birth asphyxia (61.7%). They advocated early detection of these factors to potentially prevent NDDs in children (Belhaouari et al, 2020). Similarly, Gopalkrishnan et al (2020) examined the association between NDDs and various risk factors in high socioeconomic families.…”
Section: Comorbid Familial Confounding and Environmental Risk Factorsmentioning
confidence: 99%